AGROTECHNOLOGУ OF SMALL-VOLUME AND NON-SOIL INTENSE LIGHT-CULTURE IN CUCUMBER - L. M. Anikina; P. Y. Kononchuk; V. L. Sudakov; O. R. Udalova; Y. V. Khomyakov (Овощи России, 2017)
Technology  of  intense  light-culture   has  been  developed to grow different crops under controlled environmental conditions  with  the use of specialized vegetation  apparatus  (VSU). In  the  specialized  vegetation apparatus,  designed  to   grow   plants  of   cucumber, tomato  and leafy crops, the formation of optimal light condition is constructively made with application of separate powerful lamps that have the same or different spectral quality irradiance, providing  the high illuminance,  60-90  W/m2  PAR on  cultivated  plants.  The vertical vegetation apparatus were used to develop technology of intense light-culture  in cucumber. Three modifications of vertical vegetation apparatus differing in  soil blocks  and  the  way of  nutrient  supply  to  root habitation area were elaborated to grow  the plants of cucumber.  The  development  of  cucumber  plants  in three apparatus modifications  was carried out  by one stem,  where  the  growth  was  limited  by  the  sizes of apparatus to  1.8 meter. The result of development  of small-volume and non-soil technology of intense lightculture in cucumber was presented in the article. This technology provides high productivity of plant being grown and reduces the ecological problems related to waste treatment. The application of technology of intense light-culture  in cucumber  assists the plants to realize a biological  potential and to  reach the highest productivity.  The observed plant products  are of high quality without  pesticides  and other harmful contaminants. The nitrate content  in young fruits was significantly lower the threshold allowable concentration (TAC). The basic  principles  of  intense  technology  of light-culture can be used for economically profitable enterprises  for  production  of  raw  material needs  for pharmaceutical and perfumery industries, and to  produce vitamin products  in small volumes for kindergardens, hospitals, schools and private housekeeping.